FORMULATION AND EVALUATION OF IMMEDIATE RELEASE TABLET OF ROSUVASTATIN CALCIUM BY LIQUISOLID COMPACT TECHNIQUE - Suthar, Manishkumar J.; Raval, Mr. Anil; Pate, Dr. Ravi R.; . Patel, Dr. L. D (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The in-vitro dissolution property of poorly water soluble Rosuvastatin calcium was improvedby exploring the potential of Liquisolid compact technique. In this technique, liquidmedications of water-insoluble drugs in liquid vehicles (non-volatile solvents) can beconverted into acceptably flowing and compressible powders. Different liquisolid compactswere prepared using the required quantities of powder and liquid ingredients to produceacceptably flowable and compressible admixture. To improve aqueous solubility as well aspoor dissolution rate of Rosuvastatin calcium, Propylene glycol was selected as non- volatileSolvent, Anhydrous dibasic calcium phosphate and Syloid 244FP was selected as carrier andcoating material respectively. The formulated liquisolid system were evaluated for theirvarious pre-compression and post-compression parameters. From the results, it was foundthat solubility and drug release increased with lower drug concentration. Optimizedformulation LS1 showed satisfactory results of cumulative percentage release (88.98±0.80%at 30 min., 98.27±2.0% at 60 min.). The selected formulation (LS1) was found to be stable at40 ± 0.5 °C and 75 ± 5% RH during the test period of 1 month. From this study it concludesthat, the liquisolid technique is a promising technique for improvement of dissolutionproperty of poorly water-soluble drugs and formulating immediate release solid dosageforms